2004
DOI: 10.1128/ec.3.4.919-931.2004
|View full text |Cite
|
Sign up to set email alerts
|

Gpr1, a Putative G-Protein-Coupled Receptor, Regulates Morphogenesis and Hypha Formation in the Pathogenic Fungus Candida albicans

Abstract: In response to various extracellular signals, the morphology of the human fungal pathogen Candida albicans switches from yeast to hypha form. Here, we report that GPR1 encoding a putative G-protein-coupled receptor and GPA2 encoding a G␣ subunit are required for hypha formation and morphogenesis in C. albicans. Mutants lacking Gpr1 (gpr1/gpr1) or Gpa2 (gpa2/gpa2) are defective in hypha formation and morphogenesis on solid hypha-inducing media. These phenotypic defects in solid cultures are suppressed by exogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
124
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 51 publications
3
124
2
Order By: Relevance
“…4E). Cells constitutively overexpressing the G protein-coupled receptor Gpr1 become hyperfilamentous on solid Spider media by PKA stimulation (26,28), and we observed that filastatin blocked hyphal morphogenesis in these cells (Fig. 4A).…”
Section: Filastatin Inhibits Induction Of Hyphal Morphogenesis By Mulmentioning
confidence: 86%
“…4E). Cells constitutively overexpressing the G protein-coupled receptor Gpr1 become hyperfilamentous on solid Spider media by PKA stimulation (26,28), and we observed that filastatin blocked hyphal morphogenesis in these cells (Fig. 4A).…”
Section: Filastatin Inhibits Induction Of Hyphal Morphogenesis By Mulmentioning
confidence: 86%
“…CO 2 /HCO 3 2 directly stimulates Cyr1p activity by binding to the catalytic domain of Cyr1 (Klengel et al 2005). The cyclase activity is also regulated by the small GTPases (Ras1, Ras2), G-protein coupled receptor Gpr1, and Ga protein Gpa2 in response to nutrients (Feng et al 1999;Sanchez-Martinez and PerezMartin 2002;Miwa et al 2004;Maidan et al 2005a;Zhu et al 2009). Gpr1 in C. albicans is responsive to methionine, but not to glucose (Maidan et al 2005b), suggesting that this signal is likely encountered by this fungus in vivo.…”
Section: Environmental Regulation Of Hyphal Morphogenesis Sensing Nutmentioning
confidence: 99%
“…The cyclase activity is regulated by two G proteins, Ras1 and Gpa2, in C. albicans (Feng et al, 1999;Sanchez-Martinez and Perez-Martin, 2002;Miwa et al, 2004;Maidan et al, 2005). ras1 mutants are defective for hyphal formation under induction with serum filtrate in liquid media (Feng et al, 1999), whereas gpa2 mutants are defective in hyphal growth on solid hyphal-inducing media (Miwa et al, 2004;Maidan et al, 2005). The G proteins act through PKA to induce morphogenesis in C. albicans.…”
Section: Introductionmentioning
confidence: 99%
“…The adenylate cyclase Cdc35 and its associated protein Cap1 are required for hyphal development under all hyphal-inducing conditions, including serum (Bahn and Sundstrom, 2001;Rocha et al, 2001). The cyclase activity is regulated by two G proteins, Ras1 and Gpa2, in C. albicans (Feng et al, 1999;Sanchez-Martinez and Perez-Martin, 2002;Miwa et al, 2004;Maidan et al, 2005). ras1 mutants are defective for hyphal formation under induction with serum filtrate in liquid media (Feng et al, 1999), whereas gpa2 mutants are defective in hyphal growth on solid hyphal-inducing media (Miwa et al, 2004;Maidan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%